2014
DOI: 10.15586/jkcvhl.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EGFR, KRAS and BRAF gene mutations in renal cell carcinoma

Abstract: A subset of renal cell carcinoma (RCC) patients has been shown to respond to anti-EGFR therapy. As KRAS and BRAF mutations are associated with poor response to anti-EGFR therapy in some cancers, it has been suggested that screening for KRAS and BRAF mutations in RCC may be a promising strategy to identify patients who might respond to EGFR-targeted therapy. The aim of this study was to investigate the mutation status of EGFR, KRAS and BRAF in RCC patients. Renal tumors and normal renal samples from forty-eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Maybe it is because PIK3CA mutations are rare in ccRCC and are present only in 2-5% of tumors [46] or result from intratumoral molecular heterogeneity which should be studied by novel sampling strategies [47]. Similarly to other authors [47][48][49][50] we also did not detect mutations in KRAS gene. It seems that mutations in PIK3CA and KRAS are not significant events in the development of ccRCC.…”
Section: Emt In Localized Ccrccsupporting
confidence: 70%
“…Maybe it is because PIK3CA mutations are rare in ccRCC and are present only in 2-5% of tumors [46] or result from intratumoral molecular heterogeneity which should be studied by novel sampling strategies [47]. Similarly to other authors [47][48][49][50] we also did not detect mutations in KRAS gene. It seems that mutations in PIK3CA and KRAS are not significant events in the development of ccRCC.…”
Section: Emt In Localized Ccrccsupporting
confidence: 70%
“…Previous studies using NGS have revealed the occurrence of evolutionary convergent phenotypic events, despite divergent genotypic alterations, in genes related to cRCC pathogenesis, including distinct mutations in genes involved in the PI3K-AKT-mTOR pathway, chromatin remodeling, and the VHL-HIF pathway (Voss et al, 2014; Riazalhosseini and Lathrop, 2016). Studies have also shown that the EGFR protein is overexpressed in both primary and metastatic RCC (Bayrak et al, 2014).…”
Section: Molecular Signatures Of Oeff Specimens Tested By Ocav1mentioning
confidence: 99%
“…Regions prone to high systematic errors can be defined based on technical limitations of an NGS platform and validation data. For instance, variants in homopolymer regions, genes with high homology to pseudogenes or within repetitive regions are some of the sources for systematic errors (Bragg et al, 2013; Bayrak et al, 2014; Damiati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The same situation has been observed in renal cell carcinomas. Hence, KRAS mutations do not appear to play a major role in these types of tumors [13], but several studies have revealed that KRAS overexpression is a frequent event in these tumors [14]. Here, restoration of miR-216b inhibits KRAS protein level in ccRCC cells (Fig.…”
Section: Discussionmentioning
confidence: 92%